Pengaruh Kekurangan Kalsium Pre-Postnatal terhadap Kepadatan Gigi dalam Menunjang Perawatan Ortodontik Studi Eksperimental Laboratoris pada Tikus - Pinandi Sri Pudyani (Faculty of Dentistry, Universitas Indonesia, 2015)
The knowledge of the growth and development factors in orthodontics is needed because skeletal manipulations are often done in orthodontic treatment. Because of that, knowledge and understanding of the concept of physiological growth by age especially in the face is needed, apart from growth and development of the teeth. The purpose of this study was to investigate the influence of pre and postnatal calcium deficiency on the density of teeth. Density of teeth was measured by calcium and phosphorus concentration and right incisivus maxilla weight. The study was carried on 30 Rattus norvegicus rats, divided in 3 groups. The first group was fed by a diet without calcium postnatal, the second group was fed by a diet without pre and postnatal calcium, and the third group was fed by standard diet. The concentration of calcium was measured by AAS (Atomic absorption spectrophotometric analysis), the right incisivus maxilla was measured in milligrams, and phosphorus concentration by ultraviolet spectrophotometry. The results of the study showed a significant difference (p<0,01), in calcium and phosphorus concentration and right incisivus maxilla weight between the non calcium fed postnatal, pre-postnatal and the standard groups.